ANALISA DURASI LAMPU LALU LINTAS MENGGUNAKAN METODE SIMULASI - Tama, Ishardita Pambudi; Sari, Ratih Ardia; Umar, Faishol (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
With the growth of vehicle number every year, traffic congestion is an inevitable phenomena to be seen everywhere in the world. The congestion is sometime worsen due to the inaccurate duration of the traffic lamp. The goal of this research is to show how we could analyze the traffic condition of a junction using discrete simulation method and find the better traffic lamp duration. A busy junction which connect business district, suburb and educational district in Malang, was selected to be the object of this research. Models of existing system were developed using Arena, following data collection and observation on the object. Several scenarios based on various traffic light duration were analyzed. The best scenario found in this simulation analysis could predict the shorter vehicle queue on the junction